A descriptive study on the management of edentulous patients by members of the Manila Dental Society, 2009 - Francisco, Maria Patricia Z.; Aguiluz, Ma. Arlissa D.; Mendoza, Michael Antonio F. (Adviser).
This descriptive study on the management of completely edentulous patients by the members of the Manila Dental Society (MDS) aims to determine the protocol and methods used by members of the MDS in providing complete denture service to their patients. It specific objectives are to determine the socio-demographic profile of the mentioned group and to determine the practice of MDS members regarding the management of their complete denture patients. The results of the study could be important in determining the standard of care specifically in Complete Denture Prosthodontics, which is in turn important in determining culpability in court cases involving negligence. Out of the 300 dentists given a survey form through the snail mail and email, only 25 gave back the survey questionnaire, therefore making the results not generalizable to the overall population. The survey questionnaire asked the respondents questions regarding demographic data, dentist-patient interaction, materials and techniques used by the dentists, and the division of labor between the dentist and the dental laboratory. The results show that the respondents interact with the patients and react different when presented with similar situations. Some have recommended or used new technology (e.g implants, overdentures and flexible dentures) while others have not. Majority, though, use alginate and acrylic denture teeth in the fabrication of the complete dentures, and could finish the treatment within 3 to 5 appointments. Only in one aspect, the determination of patient's expectations of the treatment during the first appointment, have been unanimously agreed upon by all the respondents. From the study's findings, it was ascertained that there exists no single protocol of method used by the MDS members of the management of completely edentulous patients, as it is influenced by economic factors, the dentists' experience and the patient's choice.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Manila Dental Society (MDS).; Prosthodontics; Edentulous patient